2009
DOI: 10.1152/ajpendo.90710.2008
|View full text |Cite
|
Sign up to set email alerts
|

Berberine improves lipid dysregulation in obesity by controlling central and peripheral AMPK activity

Abstract: AMP-activated protein kinase (AMPK) plays an important role in regulating whole body energy homeostasis. Recently, it has been demonstrated that berberine (BBR) exerts antiobesity and antidiabetic effects in obese and diabetic rodent models through the activation of AMPK in peripheral tissues. Here we show that BBR improves lipid dysregulation and fatty liver in obese mice through central and peripheral actions. In obese db/db and ob/ob mice, BBR treatment reduced liver weight, hepatic and plasma triglyceride,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
150
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 44 publications
16
150
3
Order By: Relevance
“…Although, our 3-month treatment period led to decrease in concentrations of insulin and androgens as it was reported elsewhere (11,12,32,33), we could not confirm significant effect of MET on weight change and lipid profile as it was shown by others (11,12,34). Three months may be too short a time to demonstrate the effect of MET on metabolic abnormalities sufficiently.…”
Section: Discussioncontrasting
confidence: 61%
“…Although, our 3-month treatment period led to decrease in concentrations of insulin and androgens as it was reported elsewhere (11,12,32,33), we could not confirm significant effect of MET on weight change and lipid profile as it was shown by others (11,12,34). Three months may be too short a time to demonstrate the effect of MET on metabolic abnormalities sufficiently.…”
Section: Discussioncontrasting
confidence: 61%
“…However, reversed gene expression alterations were observed in berberine-treated diabetic hamsters. These gene expression alterations imply that the increased hepatic key gluconeogenic genes expression such as PEPCK, G-6-Pase and PGC-1α in diabetic hamster, which help to induce the development of insulin resistance and the onset of diabetes [18], is possibly downregulated by the increased LXRα to reduce hepatic gluconeo- Recently, Kim WS et al [28] have shown that berberine-induced improvement of hyperlipidemia and fatty liver by intraperitoneal administration in obese animals including db/db and ob/ob mice is mediated by activation of AMP-activated protein kinase (AMPK) through increasing the phosphorylation levels of AMPK in peripheral tissues, notably liver and muscle, accompanied by changes in gene expression programs involved in lipid metabolism. In this study, we used the non-genetic type 2 diabetic hamsters to investigate the beneficial effects of berberine on FIHIR.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid oxidation assays were performed as previously described, with modifications (Kim et al, 2009). Briefly, cells were incubated in α-minimal essential medium (α-MEM; Hyclone) containing 0.1 mM of 9,10-[ 3 H] palmitate (5 μCi/ml, Perkin Elmer) and 2% bovine serum albumin for 24 h. After incubation, the medium was precipitated with an equal volume of 10% trichloroacetic acid (Sigma).…”
Section: Fatty Acid Oxidation Assaymentioning
confidence: 99%